Dampak Kekerasan dalam Rumah Tangga Terhadap Kesehatan Mental Korban - Putra, Guevara Julius Sabirin (CV WAHANA PUBLIKASI, 2022)
Domestic violence (KDRT) can have a psychological impact on the victim. These include physical, sexual, psychological misery or suffering, including threats to commit acts, as well as coercion or deprivation of legal freedom within the household. Victims of domestic violence can experience a series of problems both physically and psychologically. When the impact disturbs the peace of life and threatens the victim's life, this must be dealt with immediately. The impact of this mental violence causes trauma to the victim which results in the victim always remembering the bad incident they experienced so that the victim suffers from their own thoughts. Domestic violence often involves children being dragged along and becoming victims of violence. This research aims to understand in depth the impact of domestic violence on the mental health of victims and to describe factually the psychological condition of victims of domestic violence. This research uses juridical research methods by means of studying library materials or secondary data and this research uses a normative juridical approach. The results of this research show that legally normatively there are still many acts of domestic violence (KDRT) that still occur in everyday life, even though there are laws that regulate acts of domestic violence (KDRT). From this research, conclusions can be drawn. about the importance of paying more attention to victims of domestic violence (KDRT), because for victims of domestic violence the attention they receive is very helpful in developing the mental health of victims of domestic violence.